Chlorophyll fluorescence and biomass partitioning within light and nitrogen deficiency: An example of the use of the R programming language for teaching (UNED Research Journal, 2020)
Introduction: Chlorophyll Fluorescence (Fv/Fm) detects damage in photosystem II (PSII) in plants exposed to stress (biotic and/or abiotic). Objective: In this context, Fv/Fm for the diagnosis of the effect of N deficiency and light in tomato plants (Solanum lycopersicum) was evaluated. Methods: We used the software R to analyze data from an experiment consisted of two light treatments (high and low) and two Hoagland nutritive solutions (N deficiency: (-)N; and complete solution: C). Twenty tomato plants within the two light treatments, with two nutrient levels ((-)N and C) were used. For four weeks, weekly measurements for height (H), leaf number (NL), and Fv/Fm were made. On the fourth week, the dry mass partitioning (root: RMR; stem: SMR; and leaves: LMR) and chlorophyll concentration (a, b, a/b, and total) was measured. Results: We found statistically significant differences between treatments for H, NL and Fv/Fm (KW> 14,5, g.l.= 3,76, P
Keywords: chlorophyll fluorescence; dry mass partitioning; nitrogen deficiency; light; tomato